Bone mass recovery of osteopenic vitamin D insufficient rats from strontium ranelate treatment: Does the response depend on vitamin D nutritional status or on source of vitamin D (D2 versus D3)? - Gonzales Chaves, Macarena Maria Sol (2010)
It was investigated if Vitamin D (Vit D) status or source (Vitamin D2 vs. Vitamin D3) interferes with bone mass recovery from strontium ranelate (SrRa) treatment of rats with Vit D insufficiency and established osteopenia. Osteopenic and Vit D insufficient rats were divided in groups to complete a 105-day period. First experiment: The rats were fed with diets that only varied in Vit D (100 vs. 0 IU%) and/or SrRa (0 vs. 900 mg/kg/day) content. A SHAM group received Vit D throughout the experience. Second experiment: Rats were divided into groups and received Vit D2 or Vit D3 through diet and SrRa by gavages in a fasting state. Two SHAM groups received Vit D2 or Vit D3 throughout the study. Results: Levels of 25-hydroxyvitamin 25OHD were reduced in groups lacking dietary Vit D (p < 0.001). Independently of Vit D status or source, SrRa did not affect body weight gain or bone alkaline phosphatase levels; osteocalcin and C-terminal telopeptide of type I collagen levels were reduced (p < 0.05) and bone Sr content was increased (p < 0.0001). Although no improvement in biomechanical parameters was observed, total skeletal bone mineral content and proximal tibial bone mineral density were increased (p < 0.05). There was a reduction in the trabecular number and an increase in the trabecular surface and bone volume without reaching SHAM levels. Conclusion: This is the first study that examined SrRa effects in an osteopenic vitamin Dinsufficient experimental model. Under our experimental conditions, SrRa increased bone Sr content independently of Vit D status or source; however, no evidence of an anabolic or antifracture effect was found, and only a slight decrease in some bone resorption parameters was observed. © 2010 World Scientific Publishing Company.